Features of adaptation and meat qualities of Aberdeen-Angus bulls on the background of immunostimulation. Issue 1 (January 2020) - Semenov, V; Baimukanov, D; Tyurin, V; Kuznetsov, A; Tsarevsky, I; Nikitin, D; Efimova, I
Abstract: The feasibility of using Prevention-N-E, a newly developed and tested biological product, in comparison with the previously tested PS-6 preparation in the adaptive technology of keeping specialized beef cattle of imported breeding, had been scientifically substantiated and experimentally proved. Against the background of the use of drugs in animals of the 1 st and 2 nd experimental groups, the incidence of the digestive and respiratory organs decreased by 1.4 and 2.3 times, the recovery time reduced by 3.36 and 4.88 days, accordingly, compared with the control (P <0.05). By the end of the growing period, the animals of the 1 st and 2 nd experimental groups exceeded in live weight control subjects by 6.6 and 9.2 kg, rearing by 10.4 and 14.8 kg, and fattening by 14.2 and 22.2 kg respectively. In the cuts of the carcasses of bulls of the 1 st and 2nd experimental groups, there was a bigger amount of the highest grade flesh: in spin-breast – by 1.0 and 1.0 kg, in the lumbar – by 0.2 and 0.4 kg, and in the hip – by 2.3 and 4.2 kg, rather than in the control.